Ecological and economic determinants of agricultural land value in the de-occupied territories of brovary district - Zholkiewski, E. (Land Management, Cadastre and Land Monitoring, 2026)
The article presents a comprehensive study aimed at the theoretical substantiation and assessment of ecological and economic determinants of agricultural land value formation in de-occupied territories (using the Brovary district of the Kyiv region as a case study). The relevance of the research is driven by the necessity for an objective evaluation of land assets directly affected by hostilities. To achieve the research objectives, a comparative analysis of market prices was conducted, contrasting the pre-war period (2021–2022) with the post-occupation period (2024–2025) based on secondary market data.The results of the analysis revealed a significant decrease in the average value of agricultural land. It was determined that different types of land use in this category experienced different decreases in value. Key ecological and economic factors that affect the change in the value of land were identified and substantiated, in particular, technogenic pollution as a result of military actions and changes in the structure of the offer market. The study also took into account the factor of the high cost of demining and, if necessary, reclamation of agricultural land.The results of the study emphasize the heterogeneity of the impact of war on different types of agricultural lands and indicate the need to develop comprehensive programs of restoration, reclamation and economic stimulation to increase the investment attractiveness of these territories.Received: 09.12.2025;Accepted: 18.03.2026
Keywords: humanitarian demining; technogenic soil pollution; Russian military aggression; de-occupied territories; agricultural land; land market pricing; land market value; ecological and economic assessment